Pengaruh Persepsi Risiko, Efikasi Keuangan, dan Perkembangan Financial Technology terhadap Minat Mahasiswa Berinvestasi di Pasar Modal - Sholaahuddin, Amiin; Suyanto, Suyanto; Darmayanti, Elmira Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze the effect of Perceived Risk, Financial Efficacy, and Development of Financial Technology on Student Interests Investing in the Capital Market among students of the Faculty of Economics and Business, University of Muhammadiyah Metro. The type of research used in this research is quantitative. The data used in this study is primary data with data collection techniques using questionnaires with a population of 1063 respondents from students of the Faculty of Economics and Business, University of Muhammadiyah Metro then the sampling technique in this research uses the slovin formula to determine the number of samples so that 265 respondents are obtained. The results of this study indicate that Perceived Risk has no effect on Student Interests Investing in the Capital Market, Financial Efficacy influences Student Interests Investing in the Capital Market, Developments in Financial Technology affect Student Interests Investing in the Capital Market, and Perception of Risk, Financial Efficacy, and Development of Financial Technology had a joint effect on Student Interests Investing in the Capital Market in students of the Faculty of Economics and Business, University of Muhammadiyah Metro.